Effectiveness of Credit Restructuring Strategies on Loan Recovery (Journal of Innovative Research, 2025)
Credit restructuring techniques emerged into operations as a versatile, strategic resource in mitigating financial pressures and boosting loan recovery to borrowers during periods of economic turmoil. Further, inadequate knowledge about the impact of the credit restructuring strategies could lead to Kenya’s inefficient credit financial system. The objectives of this study were: To assess the impact of credit restructuring on the loan recovery of commercial banks. In this case, the influence of extension of repayment periods, reduction in the interest rates, postponement on the repayment of the principal amounts, consolidation of payments, and extension of balloon payment is considered. The target population was 348 employees in the credit section of 30 commercial banks operating in Kenya. For this research, the technique of Simple Random Sampling was adopted to sample 186 employees from the banks. Thus, employing an explanatory research design. It was concluded that credit restructuring strategies particularly; extended repayment period, interest rate reduction, principal forbearance, debt consolidation, and extension of balloon payment period have positive and significant impacts on the loan recovery of the commercial banks. Hence, it is advised that commercial banks embrace or advance these credit restructuring approaches towards achieving better improvement of loan recovery.